PUXIRÕES E MUTIRÕES COMO MANIFESTAÇÃO DE RECIPROCIDADE EM COMUNIDADES FAXINALENSES DE REBOUÇAS – PR (1970 – 2015) - FERREIRA, WELLERSON EMANUEL (2021)
The present research seeks to analyze the manifestations of reciprocity contemplated in faxinal communities in the municipality of Rebouças, Paraná, considering the reciprocal practices in their diversity, but with a specific focus on the relations of reciprocal exchange of work called puxirões and mutirões . We seek to encompass and reflect on the changes, alterations and permanences that these reciprocal relations have had over time in the daily life of traditional faxinal communities, using photographs from the past and the present, as well as oral sources through interviews with the inhabitants of faxinals. The temporal delimitation is taken from the second half of the twentieth century, more precisely from the 1970s to 2015. The spatial cut considered refers to two faxinal communities located in the municipality of Rebouças-PR, namely Faxinal do Salto and Faxinal Marmeleiro de Cima, which are considered active faxinals. The faxinais correspond to a traditional and communitarian form of organization, having as one of its main characteristics the traditional division between raising lands and planting lands, where in the raising lands is located the common livestock house, also called community, (Floresta Ombrófila Mista-FOM) in this way, therefore, when considering the current rural scenario in the south-central region of Paraná, the active faxinais have been constituting a peculiar organizational configuration in the rural area of Paraná. Being the communitarian living and coexistence a considerable cultural highlight of these communities, the helping relationships exchanged in a reciprocal way occur in varied ways in the daily faxinalense, however, when we focus on the work performed in considerable numbers of faxinalenses, the "puxirões" or "mutirões", the main intentions of these were given by a search for fast and efficient work in a context where it was difficult in these communities the possibility of acquiring machinery and, it is worth mentioning the possibility of relaxing moments that involved a day of work in puxirões. Consequently, as time went by, some faxinalenses started acquiring tractors, which gradually culminated in the decrease of "puxirões" (pulling tractors) performed on the plantation lands, where this practice of exchanging work in a reciprocal way commonly occurred. Nowadays, the "puxirões" are still practiced, however, focused on the needs of the community as a whole, that is, occurring mainly in the raising lands, due to the mechanization process of agricultural production, portrayed and analyzed through photographs and oral reports in this research. Among the methodological procedures and sources used to carry out this research, we highlight the use of old and recent photographs (the use of both is aimed at demonstrating and reflecting on the changes in the practice of puxirões), bibliographic analysis, field research (while it was possible due to the Covid-19 pandemic) and oral reports conceived in some interviews provided by the residents of faxinal communities. Thus, it was possible to delineate a series of transformations that have occurred in the researched faxinals through a cultural perception involving the practice of reciprocal relations present in these communities; to present some considerations, especially regarding the economic changes that have affected the "puxirões", and to demonstrate how, despite suffering alterations, the "puxirões" are one of the main characteristics of community living in faxinals, since, despite suffering changes, they are still cultivated.